Eksistensi Penerapan Keadilan Restoratif Melalui Mediasi Penal Perspektif Maslahah Mursalah di Indonesia - Ahmad Wildan Rofrofil Akmal (Fakultas Hukum Universitas Islam Malang, 2024)
Implementation of penal mediation from the police to the courts must be supported by clear legal regulations to ensure that the concept of restorative justice can be properly realised. The principle of restorative justice emphasises the importance of the judiciary in sharpening legal analysis and strengthening the instinct of justice based on human consciousness and moral values. The purpose of this study is to determine the existence of the application of restorative justice through penal mediation from the perspective of maslahah mursalah hajjiyah in Indonesia. This research uses normative juridical research, using statutory and conceptual approaches.. The results of the research found the existence of penal mediation is in accordance with the concept of fulfilling maslahah mursalah hajjiyah which is all forms of actions and actions that aren’t related to other bases needed by the community, this penal mediation is in accordance with the concept of fulfilling maslahah mursalah hajjiyah.